2019
DOI: 10.1002/jsfa.9613
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the ethylene‐related signal‐inhibiting octapeptide NOP‐1 on postharvest ripening and quality of ‘Golden Delicious’ apples

Abstract: BACKGROUND Processes extending the shelf life of climacteric fruit play an important role in terms of a sustainable global food supply. In a previous study, a synthetic octapeptide (NOP‐1) was shown to inhibit the interaction between ethylene receptor (ETR) and ethylene insensitive‐2 (EIN2), and in consequence delay tomato ripening. We investigated for the first time the effect of NOP‐1 on inhibiting the ripening of apples (‘Golden Delicious’) during postharvest. RESULTS Using purified recombinant proteins fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The postharvest technologies of controlling ethylene and the ethylene pathway have been extensively studied [5, 10, 11] .1-Methylcyclopropene (1-MCP) is an ethylene receptor inhibitor and a non-toxic antagonist of ethylene that has been employed to increase the shelf life of various climacteric and non-climacteric fruits by effectively delaying fruit ripening and softening [5, 1217]. By binding to ethylene receptors, 1-MCP acts as an efficient antagonist and exerts a persistent effect.…”
Section: Introductionmentioning
confidence: 99%
“…The postharvest technologies of controlling ethylene and the ethylene pathway have been extensively studied [5, 10, 11] .1-Methylcyclopropene (1-MCP) is an ethylene receptor inhibitor and a non-toxic antagonist of ethylene that has been employed to increase the shelf life of various climacteric and non-climacteric fruits by effectively delaying fruit ripening and softening [5, 1217]. By binding to ethylene receptors, 1-MCP acts as an efficient antagonist and exerts a persistent effect.…”
Section: Introductionmentioning
confidence: 99%
“…When applied to the plant, the peptide showed visible effects on plant ethylene responses. NOP-1 successfully delayed ripening and senescence in tomatoes [ 48 , 70 ], broccoli [ 71 ], and apples [ 72 ] by six to eight days. Binding studies by MST on purified ETR receptors from tomato, apple, and Arabidopsis demonstrated the peptide’s high affinity for binding to receptors in the range of 80–100 nM [ 37 , 48 , 70 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…NOP-1 successfully delayed ripening and senescence in tomatoes [ 48 , 70 ], broccoli [ 71 ], and apples [ 72 ] by six to eight days. Binding studies by MST on purified ETR receptors from tomato, apple, and Arabidopsis demonstrated the peptide’s high affinity for binding to receptors in the range of 80–100 nM [ 37 , 48 , 70 , 72 ]. Extending the sequence of the NOP-1 inhibitory peptide with additional residues (12 aa) adjacent to the NLS binding motif in the EIN2 downstream interaction partner (NIP peptide) further improved binding affinity [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pigment changes during Japanese dogwood fruit development can be associated with the shift of colour from green‐orange hues, known to be generated by chlorophyll and carotenoid compounds, 39 to red tones, defined by anthocyanin pigments. Chlorophyll breakdown is common in latter stages of fruit development and has previously been investigated in apple, persimmon and several other fruit species 39–41 …”
Section: Resultsmentioning
confidence: 99%
“…Chlorophyll breakdown is common in latter stages of fruit development and has previously been investigated in apple, persimmon and several other fruit species. [39][40][41] Data on lipophilic antioxidants in lesser-known fruit species are very scarce and no study has ever reported their composition in Cornus fruit. Lower contents of tocopherols and plastid pigments have been reported for Sorbus aria and Sorbus aucuparia fruits.…”
Section: Tocopherols and Plastid Pigmentsmentioning
confidence: 99%